Preparation and photoluminescence enhancement of Au nanoparticles with ultra‐broad plasmonic absorption in glasses. Issue 7 (25th January 2019) - Yu, Chengye; Yang, Zhengwen; Zhao, Jingyuan; Huang, Anjun; Qiu, Jianbei; Song, Zhiguo; Zhou, Dacheng; Liu, Bitao
Abstract: The metal nanoparticles with ultra‐broad localized surface plasmonic resonance (LSPR) absorption have been widely used to enhance the up conversion luminescence (UCL) of rare‐earth doped nanoparticles. However, there have been no reports on the preparation of metal nanoparticles with the ultra‐broad LSPR in the glasses. In this work, the gold nanoparticles with the ultra‐broad LSPR were prepared for the first time in the rare‐earth doped tellurite glasses by the high‐temperature melting method, and the influence of ultra‐broad LSPR on the UCL of Er 3+ –Yb 3+ and Er 3+ –Yb 3+ –Nd 3+ co‐doped tellurite glasses was investigated upon 980 and 808 nm excitation, respectively. With the precipitation of the Au NPs, about seven and 12‐fold enhancements were obtained for the green and red UCL of Er 3+ –Yb 3+ co‐doped tellurite glasses excited at 980 nm, respectively, and about 5.9 and sevenfold enhancements were observed for the green and red UCL of Er 3+ –Yb 3+ –Nd 3+ co‐doped tellurite glasses excited at 808 nm, respectively. The UCL mechanism related to UCL enhancement was confirmed. The results demonstrated that the enhanced excitation field and the increasing rate of radiative decay were responsible for the enhancement of UCL.